Pengaruh Plant Growth Promoting Rhizobacteria dari Akar Bambu terhadap Serapan Hara N, P, K dan Produksi Tanaman Jagung di Tanah Ultisol - Aurelia, Meditha Afra; Hayati, Rita; Alhaddad, Abdul Mujib (Agrotrop : Journal on Agriculture Science, 2025)
The Effect of Plant Growth Promoting Rhizobacteria from Bamboo Roots on N, P, K Absorption and Corn Production in Ultisol Soil. Ultisol soil is widely used as a planting medium for corn, especially in West Kalimantan, but has problems with soil fertility, so it requires additional input by utilizing plant growth-promoting root bacteria which is more popularly called PGPR (Plant Growth Promotion Rhizobacteria) from bamboo plants. This study aims to determine the effect of PGPR on nutrient uptake of N, P, K and production of maize plants in Ultisol soil. This study used a non-factorial Completely Randomized Design (CRD), namely various concentrations of PGPR (Plant Growth Promoting Rhizobacteria) from bamboo roots (factor P) with 4 treatment levels, namely: P0 (no treatment), P1 (4 ml/plant), P2 (8 ml/plant), and P3 (12 ml/plant). The results showed that the PGPR (Plant Growth Promoting Rhizobacteria) treatment had a significant effect on plant dry weight, upper plant N uptake, upper plant P uptake, upper plant K uptake, and dry shell weight per plant. Application of PGPR can increase dry weight, nutrient uptake of N, P, K and maize yields on Ultisol soil. The PGPR dose had the highest value in the P2 treatment (8 ml/plant).